How do season, on-farm fasting interval and lairage period affect swine welfare, carcass and meat quality traits? - Dalla Costa, Filipe Antonio [UNESP]; Dalla Costa, Osmar Antonio; Coldebella, Arlei; de Lima, Gustavo Júlio Mello Monteiro; Ferraudo, Antonio Sérgio [UNESP] (Springer Nature, 2018)
This study was carried out in order to determine the effects of different combinations of on-farm fasting intervals (8, 12, 16, 20 h) and 1.5 h of transport plus lairage periods (1, 3, 6 h) at different seasons (summer/winter) on blood stress parameters (cortisol and lactate), stomach content and weight, skin lesion and meat quality in a total of 960 pigs from eight farms. Blood lactate levels were greater in the summer (P < 0.001) and stomach content was affected (P < 0.05) by season, on-farm fasting interval (P < 0.001), lairage time (P < 0.0001). Stomach content weight reduces as the total feed withdrawal time increases up to on-farm fasting of 17 and 1 h of lairage. Stomach content can be influenced by feed and water in different ways according to treatments. Only 8 h of on-farm fasting is not enough to empty stomachs from feed content. However, an on-farm fasting period of 16 h or longer can also increase the occurrence of more water in the stomachs. Carcass lesions caused by fighting were greater (P ≤ 0.005) in the winter, mainly after 3 and 6 h of lairage (P ≤ 0.005). Loin and ham pHu was lower (P ≤ 0.05) for pigs slaughtered after 6 h of lairage during the summer. The application of 12 h of on-farm fasting with 6 h of lairage seemed to be best combination to reduce stomach content weight (feed and water). In the winter, shorter lairage period can be used to reduce percentage of skin lesions and better pork quality traits in pigs.
Keywords: Cortisol; Feed withdrawal; Lactate; Skin lesion